Dietary Curcuma, a Powerful Epigenome Modulator in Breast Cancer: an In Silico Study - Elbasyouni, Amel; Saadi, Leila; Baha, AbdelKarim (Indonesian Society for Cancer Chemoprevention, 2022)
The inhibition of DNA methyltransferase-1 enzyme can strongly decrease the capacity of cells to enhance the tumour-genesis process. Members of the Estrogen-Related Receptors family regulate several elements of cellular metabolism. These are orphan nuclear receptors that regulate a wide range of functional gene networks involved in breast carcinogenesis and the regulation of associated methionine and folate cycles, providing a proven direct relationship to DNA methylation as a result. Moreover, dietary phytochemicals, such as Curcumin, can involve epigenetic modification, which may decrease the development of many types of cancer, especially breast cancer in women. We conducted this study to investigate the effect of Curcuma (PubChem ID: 969516) on the epigenetic modification and inhibition of the DNA methyltransferase-1 (PDB ID: 3PTA) activity and Estrogen-Related Receptors (PDB ID: 1XB7) using Molecular docking approach and computational tools that may inform whether the Curcuma could provide this protective anticancer effect or not. Interestingly, the DNA methyltrasferase1-Curcumin and Estrogen-Related Receptors-Curcumin complexes display a docking score of -6.9 and -7.1 kcal/mol, respectively. Furthermore, Curcumin displays hydrogen, Pi-Cation, Pi-Anion and Van der Waals bonds with active site residues of the targeted molecules. By targeting DNA methylation via the combined inhibition of estrogen-related receptors and DNMT1, our research opens up a new therapeutic path for breast cancer treatment.Keywords: curcumin, breast cancer, epigenetic, molecular docking, treatment.